SUSTAINABLE WATER MANAGEMENT FOR WATER SUPPLY EFFICIENCY: A CASE STUDY AT SYARIKAT AIR MELAKA BERHAD - Tengku Azzlan, Tengku Ahmad Farid; Boon Cheong, Chew; Lau, Keng Liang (Journal of Technology Management and Business, 2016)
Water use has been growing at more than twice than rate of population growth in last century.Â  This level of population growth will result in increased demand for potential water from agriculture, industrial and domestic sectors of the economy. Rapidly rising demand and falling supplies of fresh water are leaving ever more nations to face chronic water shortages. The objective of this research is examined current water management systems in Syarikat Air Melaka Berhad (SAMB), assessing how far the current systems manage to keep the water sustainably. This research aimed to identify the effectiveness of programs implemented by the SAMB to sustain the water supply. Furthermore, this research aimed to formulate and propose improvements and enhancements for better water management systems. This research is beneficial for the government, university and the public. The research is been conducted at Syarikat Air Melaka Berhad (SAMB) through interviews of thirty respondents. From there, researcher gained crucial information and point of view from the managerial perspective and also technical and technology insight regarding sustainable water management at SAMB.